2012
DOI: 10.1002/ase.1304
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the willingness for cadaveric donation in Greece: A population‐based study

Abstract: Despite the importance of body donation for medical education and the advancement of medical science, cadaveric donation remains suboptimal worldwide. The purpose of this study was to evaluate the willingness of body donation in Greece and determine the characteristics of donors. This cross-sectional questionnaire survey was conducted from January to June 2011. A specially designed questionnaire was distributed to 1,700 individuals who were randomly selected from five major Greek cities. It was found that high… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
42
2
4

Year Published

2013
2013
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(56 citation statements)
references
References 38 publications
3
42
2
4
Order By: Relevance
“…When divided in two groupsatheist/agnostics on the one hand and religious students on the other, the former group was significantly more likely to become body donors. Studies carried out in Greece, Turkey and Australia revealed a similar attitudinal pattern (ŞEHIRLI, Attitudes of medical and allied medical… SRDIĆ GALIĆ, B.; DRVENDŽIJA, Z.; ŠTRKALJ, G. SAKA, SARIKAYA, 2004;HALOU et al, 2013;ALEXANDER et al, 2014). However, the simple dichotomy -atheist/agnostic generally in favor and religious individuals against self-body donation -is a simplification as the patterns of influence seem to be more complex.…”
Section: Discussionmentioning
confidence: 95%
“…When divided in two groupsatheist/agnostics on the one hand and religious students on the other, the former group was significantly more likely to become body donors. Studies carried out in Greece, Turkey and Australia revealed a similar attitudinal pattern (ŞEHIRLI, Attitudes of medical and allied medical… SRDIĆ GALIĆ, B.; DRVENDŽIJA, Z.; ŠTRKALJ, G. SAKA, SARIKAYA, 2004;HALOU et al, 2013;ALEXANDER et al, 2014). However, the simple dichotomy -atheist/agnostic generally in favor and religious individuals against self-body donation -is a simplification as the patterns of influence seem to be more complex.…”
Section: Discussionmentioning
confidence: 95%
“…Studies have included retrospective descriptions of donors whose deceased body had already been donated (Dluzen, Brammer, Bernard & Keyser, 1996); of living registered donors (Bolt et al, 2010;Cornwall, et al, 2012a;McClea & Stringer, 2010;Wijbenga et al, 2010); and of enquiring potential donors (Richardson & Hurwitz, 1995). In addition, prospective random selection studies of the general community have assessed characteristics of donors and their willingness to donate (Boulware et al, 2004;Halou et al, 2013;Rokade & Gaikawad, 2012).…”
mentioning
confidence: 98%
“…Ethnicity among deceased donors was almost exclusively white Caucasian (e.g., Dluzen et al, 1996). Religious organizations' past disapproval of dissection has previously negatively influenced people with religious or spiritual beliefs (Garment, Lederer, Rogers, & Boult, 2007) and increasing unwillingness to become a body donor (Boulware et al, 2004), while a significantly greater number of people with no religious affiliation have been consistently willing to become donors (Alexander, Marten, Stewart, Serafin & Strkalj, 2013;Cornwall et al, 2012a;Halou et al, 2013;Richardson & Hurwitz, 1995) or were living registered donors (Bolt et al, 2010).…”
mentioning
confidence: 98%
“…They have surveyed students, other anatomists, or the local population in Greece (Halou et al, 2013), Turkey (Gürses et al, 2018), Iran (Abbasi Asl et al, 2016), India (Saha et al, 2015), or Brazil (Simao et al, 2016) to evaluate the willingness for body donation and possible barriers to this way of getting access to bodies. And while there are cultural and religious obstacles, it turns out that often lack of awareness of the option of body donation is an additional factor.…”
Section: Of the International Federation Of Associations Of Anatomistmentioning
confidence: 99%